Piaget: La enseñanza coherente con el desarrollo cognitivo - Etcharren, Yvonne (Revista Chilena de Humanidades, 2016)
This article reviews Piaget’s fundamental conceptualizations relating them to the periods of the child’s mental development. lt emphasizes the importance of understanding the fact that the child livers a reality quite different from that of the adult. Professor Etcharren’s article also helps us through the meaning of Piaget’s complex technical terminology, which in many cases impedes the proper of his work.